An Aspergillus luchuensis isolated from a patient with hemoptysis insights from a comprehensive genome-based analysis - Kai Chang; Huajie Xie; Yanyan Wang; Xin Zhao; Wanlin Na; Ningwei Xian; Yuan Liu; Zhongyong Jiang; Chenxia Liu (Medicine, 2026)
Rationale: Asp luchuensis , a member of the A niger group, is widely used in food fermentation and rarely causes invasive pulmonary aspergillosis (IPA) in humans. Clinical cases of IPA induced by this strain are extremely scarce, and its genomic characteristics, virulence profiles, and pathogenic mechanisms remain poorly understood, resulting in insufficient clinical recognition of its invasive infection potential. Patient concerns: A 57-year-old immunocompetent non-neutropenic male patient with a long-term smoking and drinking history presented with unexplained severe cough and massive hemoptysis (approximately100 mL) without other typical infectious symptoms. Diagnoses: Combined with chest computed tomography (CT) inflammatory lesions, positive galactomannan test, fungal PCR and metagenomic next-generation sequencing results, the patient was definitively diagnosed with probable A luchuensis -induced IPA. Genomic and transcriptomic analyses confirmed the pathogen as a variant A luchuensis strain with 3 key hypervirulence genes, highly active mitochondrial energy metabolism, and no specific antifungal resistance genes. Interventions: The patient received standardized intravenous antifungal combination therapy with voriconazole and amphotericin B after confirmed diagnosis. Outcomes: The patient’s cough and hemoptysis were significantly relieved after 10 days of treatment, with stable vital signs and no adverse drug reactions or disease progression. Lessons: A luchuensis possesses strong invasive pathogenicity and can trigger IPA even in non-neutropenic immunocompetent individuals. Negative conventional microbial tests cannot exclude its infection, and mNGS is a reliable diagnostic tool. This strain is susceptible to routine antifungal drugs, and clinicians should raise awareness of atypical Asp species-induced invasive pulmonary infections.